SOFSEM 2011: Theory and Practice of Computer Science 37th Conference on Current Trends in Theory and Practice of Computer Science, Nový Smokovec, Slovakia, January 22-28, 2011. Proceedings - Cerná, Ivana; Gyimóthy, Tibor; Hromkovič, Juraj; Jeffery, Keith; Kralovic, Rastislav; Vukolic, Marko; Wolf, Stefan (Theoretical Computer Science and General Issues,, 2011)
This book constitutes the refereed proceedings of the 37th Conference on Current Trends in Theory and Practice of Computer Science, SOFSEM 2011, held in Nový, Smokovec, Slovakia in January 2011. The 41 revised full papers, presented together with 5 invited contributions, were carefully reviewed and selected from 122 submissions. SOFSEM 2011 was organized around the following four tracks: foundations of computer science; software, systems, and services; processing large datasets; and cryptography, security, and trust.